A review of Mid-Holocene hunter-gatherer occupation in the eastern Pampa-Patagonia transition of Argentina: Assessing cultural continuities and population dynamics - Gustavo Martínez; Lewis A. Owen; Gustavo Flensborg; Luciana Stoessel; Natalia Carden; Ana Paula Alcaráz; Florencia Santos Valero; Gustavo Adolfo Martínez (Quaternary Environments and Humans)
Diverse causes and explanations have been proposed to help explain the absence, scarcity, and discontinuity of Mid-Holocene archaeological records in Central Argentina. Evidence for Mid-Holocene (∼6300–4100 14C yr BP/7.4–4.8 ka) hunter-gatherers occupations have been recognized in the eastern Pampa-Patagonia transition of Argentina. Here, we review and summarize the state-of-the-art archaeological knowledge that we have generated from Mid-Holocene archaeological sites from our study area. In doing so, we describe and discuss the geoarchaeological issues and the geomorphic evidence, radiocarbon and optically stimulated luminescence dating, lithics and raw materials provenience, zooarchaeology and taphonomy, subsistence and diet, bioarchaeology, and portable art. Our main objective is to address whether the already proposed Mid-Holocene sedimentary and chronologic discontinuities produced by geologic and taphonomic biases also respond to cultural discontinuities, e.g., abandonments, decreasing human density, and changes in mobility. Material culture and the structure of the archaeological record suggest that social and behavioral characteristics of hunter-gatherer societies are similar during the Mid-Holocene and the initial Late Holocene (∼6300–1000 14C yr BP/7.4–1.0 ka). Archaeological evidence from these periods indicates effective and stable human occupation with social interaction networks operating with neighboring regions such as the Pampa and Patagonia. Even though sedimentary and chronologic discontinuities exist, cultural continuity is likely. This review contributes to the understanding of Mid-Holocene discontinuities in Central Argentina.